Survival and growth of the forage grass Festuca rubra in naturally and artificially devegetated sites in a sub-arctic coastal marsh - O, Pamela C.; Kotanen, Peter M.; Abraham, Kenneth F. (Écoscience, 2005)
This is the accepted manuscript of an article published by Taylor & Francis. The manuscript does not include figures. To view figures, please consult the publisher's version of this article. Festuca rubra is an abundant supratidal grass on sub-arctic James Bay (Canada) shorelines, forming extensive near-monocultures that are used as forage by nesting and migrating geese. Studies at other, more northern North American locations have shown grubbing by geese can have severe consequences for intertidal and supratidal marshes, but this research has focussed on plant communities that differ substantially in species composition, physical environment, and extent from James Bay's Festuca meadows. In this study, we examined the responses of this grass to natural and simulated goose grubbing in Festuca swards heavily used by Lesser Snow Geese, Canada Geese, and Brant at Akimiski Island in James Bay. We transplanted Festuca into plots previously devegetated by geese, into plots where we removed vegetation to simulate goose grubbing, and into intact vegetation (controls). We found shoots transplanted into control and artificially grubbed plots survived well, but those transplanted into previously devegetated areas usually died. Growth initially was reduced in naturally devegetated sites, but the few survivors in the following year performed as well as plants transplanted into intact or artificially grubbed sites. Spot measurements suggested that naturally devegetated sites suffered from degraded soil conditions, such as hypersalinity and increased temperature. These results provide evidence that recovery of Festuca swards following loss of vegetation is likely to be difficult, probably as a result of deteriorating soil conditions. Models of goose-plant interactions developed at substantially more northern sites thus seem applicable to the significantly different plant communities of the James Bay shoreline. This is a contribution of the Wildlife Research and Development Section of the Ontario Ministry of Natural Resources. This research was supported by an NSERC (Canada) PGS-A and Northern Research Supplement, a Richard H.G. Bonnycastle Graduate Fellowship from the Institute for Wetlands and Waterfowl Research, and the NSTP program of the Department of Indian Affairs and Northern Development (PCO); an NSERC Discovery Grant (PMK); and the Ontario Ministry of Natural Resources (KFA).